APPLICATION OF OSL METHOD IN DATING PAST EARTHQUAKES - Tsodoulos, I.; Stamoulis, K.C.; Papachristodoulou, C.; Pavlides, PS.; Ioannides, K.G. (Bulletin of the Geological Society of Greece, 2016)
The aim of this study was to establish a chronological frame of paleoseismic events of Gyrtoni Fault, (Thessaly, Central Greece), with the use of OSL dating method. The Gyrtoni Fault, defines the north-eastern boundary of the Middle-Late Quaternary Tyrnavos Basin, and was previously investigated with geological methods. Twenty five fluvial-colluvial sediment and pottery samples were collected from two paleoseismological trenches, excavated along the Gyrtoni Fault, from both the upthrown and the downthrown fault blocks. Optically Stimulated Luminescence (OSL) dating was applied to coarse grain quartz using the single-aliquot regenerative-dose (SAR) protocol. Investigations of luminescence characteristics using various tests confirmed the suitability of the material for OSL dating using the SAR protocol. Radioactivity measurements were performed in order to estimate the annual dose rate of the surrounding soils to which the quartz grains were submitted during the burial period of the collected samples. The estimated OSL ages agreed well with the available stratigraphical data, and archaeological evidence. The occurrence of three surface faulting events in a time span between 1.42 ± 0.06 ka and 5.59 ± 0.13 ka was revealed while an earlier faulting event (fourth) was also recognized to be older than 5.59 ± 0.13 ka.